The Meaning of Profit and Loss for Tobacco Farmers - Cempaka, Putri; Ridhawati, Rini; Husnaini, Wahidatul (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2025)
This study aims to reveal the meaning of profit and loss for tobacco farmers in the East Sakra subdistrict, East Lombok Regency. An interpretive paradigm with a phenomenological approach as the research method. The data collection involves passive participatory observation, in-depth interviews, and documentation of five informants from three villages who are tobacco farmers with more than ten years of experience, specific types of tobacco cultivation, and land ownership or lease. The results showed that profit is interpreted as the value of honesty when it can, a blessing, and business sustainability. At the same time, there is a loss of understanding of usefulness, sincerity, and adaptation through asset strategies, savings, or loans. As for production costs and income, farmers see profit as harvest satisfaction and business continuity, while losses drive efficiency and strategy evaluation. From an accounting perspective, farmers keep minimal records, using a cash-based approach that ignores depreciation, labour, and indirect costs. This study reveals that tobacco farmers perceive profit and loss beyond financial gain, emphasizing inner satisfaction, spiritual happiness, and social values, contrasting with conventional accounting concepts.